Facile preparation of CoMoO4 nanorods at macroporous carbon hybrid electrocatalyst for non-enzymatic glucose detection - Meng, Tianjiao; Jia, Huixian; Ye, Huimin; Zeng, Tao; Yang, Xinjian; Wang, Huan; Zhang, Yufan (Journal of colloid and interface science, 2020)
[Display omitted] •Nanorod-like CoMoO4 at MPC supports were prepared by a simple method.•CoMoO4/MPC hybrids were acted as an effective sensing platform for non-enzymatic glucose detection.•The novel CoMoO4/MPC hybrids will hold promise in development of electrode materials. Glucose is a popular biosensor target due to its closely with diabetes or hypoglycemia in blood. Designing efficiency electrocatalysts for the determination of glucose is vital to develop glucose detection devices. CoMoO4, as a kind of bimetallic oxide material, exhibits unique electrochemical properties. 3D macroporous carbon (MPC) has large specific surface area and excellent electrical conductivity, providing an effective support for loading other nano-entities to form novel composite with good synergetic effects. Herein, nanorod-like CoMoO4 anchored onto MPC support was synthesized for the development of a promising electrochemical sensing platform for glucose. Attributing to the synergic effects between the good electrocatalytic performance of CoMoO4 nanorods and the extraordinary electrical conductivity of 3D layered MPC, the novel CoMoO4/MPC composites non-enzymatic sensor shows excellent electrocatalytic performance for oxidation of glucose. Under the optimum conditions, the proposed CoMoO4/MPC hybrids provided a reliable linear range of 5 × 10−7 to 1.08 × 10−4 M with a low limit of detection (0.13 μM) for the detection of glucose. Meanwhile, the CoMoO4/MPC sensing platform shows fast response time of 1.76 s, good stability and selectivity for detecting glucose. Moreover, this non-enzymatic sensor also has been successfully applied to measure glucose level in human blood samples. Therefore, the developed sensor holds a new promise for the construction of facile and sensitive non-enzymatic glucose analytical platform.